The Virtual Token Passing Ethernet: Implementation and Experimental Results - Francisco Carreiro (2004)
This paper presents the design and first experimental results of VTPE (Virtual Token-passing Ethernet). VTPE is a deterministic protocol for real-time applications based on shared Ethernet, aimed to be used either in small processing power processors or in powerful ones. It is based on implicit token rotation similar to the virtual token-passing used in the P-NET protocol. The VTPE implementation leads to reduced program code, thus fitting in small microcontrollers memory and imposing low communication overhead.